Peran Kasih dan Altruisme terhadap ketahanan keberlanjutan Organisasi - Eryc Eryc (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study examines the influence of love and altruism on organizational resilience. With a growing emphasis on human-centric approaches in organizational management, understanding the impact of love and altruism on organizational resilience becomes increasingly crucial. Through a comprehensive literature review and empirical analysis, we investigate how these human-oriented values contribute to enhancing an organization's ability to withstand and adapt to challenges and disruptions. The findings reveal a positive and significant relationship between love, altruism, and organizational resilience. Our research sheds light on the vital role of fostering loving and altruistic cultures within organizations to cultivate resilience and thrive in an ever-changing business landscape. The implications of this study offer valuable insights for leaders and managers seeking to build resilient organizations that prioritize the well-being and support of their employees and stakeholders.